2016
DOI: 10.1016/j.athoracsur.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Volume-Outcome Associations in Adult Extracorporeal Membrane Oxygenation in the United States

Abstract: Background The aim of this study was to evaluate institutional volume-outcome relationships in extracorporeal membrane oxygenation (ECMO) with subanalyses of ECMO in patients with a primary diagnosis of respiratory failure. Methods All institutions with adult ECMO discharges in the Nationwide Inpatient Sample from 2002 to 2011 were evaluated. International Classification of Diseases (ninth revision) codes were used to identify ECMO-treated patients, indications, and concurrent procedures. Patients who were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 24 publications
2
30
0
Order By: Relevance
“…Additionally, patients transferred to high‐volume centres and subsequently placed on ECMO had both increased mortality compared to index admissions, and increased costs to the accepting medical institution . The authors did report limitations of the database, one being the lack of relevant clinical information such as whether VA‐ or VV‐ECMO was applied …”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Additionally, patients transferred to high‐volume centres and subsequently placed on ECMO had both increased mortality compared to index admissions, and increased costs to the accepting medical institution . The authors did report limitations of the database, one being the lack of relevant clinical information such as whether VA‐ or VV‐ECMO was applied …”
Section: Discussionmentioning
confidence: 59%
“…Currently, ELSO guidelines recommend a minimum of six ECMO cases per year . Controversially, recent studies from USA found that outcomes in the Nationwide Inpatient Sample did not follow the traditional volume‐outcome relationship as low‐volume ECMO centres had the lowest rates of in‐hospital mortality . Additionally, patients transferred to high‐volume centres and subsequently placed on ECMO had both increased mortality compared to index admissions, and increased costs to the accepting medical institution .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, the results of this study contradict previous findings that ECMO outcomes are not directly related to the total number of cases performed. 11,12 In addition, this study failed to report on the effect of iatrogenic, intraoperative complications on the outcomes of ECMO. Issues such as surgical misadventure or suboptimal myocardial protection can be significant drivers of mortality, and ECMO therapy often cannot salvage the situation.…”
mentioning
confidence: 90%
“…However, experience with directing ECMO cases to high-volume centers is limited, and has not been scientifically proven superior as a strategy. A recent study even suggested that lowvolume centers have better ECMO in-hospital mortality than high-volume centers [44], questioning the existence of a positive volume-outcome relationship in this population. Another unresolved issue is the nurse-to-patient ratio for ECMO patients [45].…”
Section: Regional/national Organization Of Ecmo Supportmentioning
confidence: 99%